Answer:
We have f(10) = -49.
Step-by-step explanation:
We have
![f(x)+f(2x+y)+5xy=f(3x-y)+2x^(2)+1](https://img.qammunity.org/2020/formulas/business/high-school/wk1qhx38haeafe4o0xmg9hd09a6g4an9sd.png)
Putting x = 0 and y = 0 we get,
![f(0)+f(0)+0=f(0)+0+1\\\\\therefore f(0)=1](https://img.qammunity.org/2020/formulas/business/high-school/6hh9veiz3arffjsign8w7vw41phol5izgv.png)
Now put x = 0 in the function equation we get
![f(0)+f(y)+0=f(-y)+1\\\\1+f(y)=f(-y)+1(\because f(0)=1)\\\\\Rightarrow f(-y)=f(y)](https://img.qammunity.org/2020/formulas/business/high-school/xn7m6gk1d4lznnau7b5xr9xqau4cst9rnk.png)
Hence the given function is an even function
Now put x = 2y in the functional equation we get
![f(2y)+f(5y)+10y^(2)=f(5y)+8y^(2)+1\\\\f(2y)=-2y^(2)+1\\\\](https://img.qammunity.org/2020/formulas/business/high-school/d107v75mz8udjy25jxtmm4bp88gzgm6w9z.png)
Now put y = x/2 we get
![f(x)=-2((x^(2))/(4))+1\\\\f(x)=(-x^(2))/(2)+1](https://img.qammunity.org/2020/formulas/business/high-school/hvxi08u6ic5gl74qravar7usiajgyxpc1h.png)
Thus f(10) equals
![f(10)=(-100)/(2)+1](https://img.qammunity.org/2020/formulas/business/high-school/swgx6k11geiskjujd195j430eugf16n5ga.png)
thus f(10) = -49